Management of health-care waste in Izmir, Turkey - Ahmet Soysal; Hatice Simsek; Dilek Soysal; Funda Alyu (Annali dell'Istituto Superiore di Sanità, 2010)
The aim of this study was to evaluate health-care waste in the 18 districts of metropolitan municipality of the third biggest city in Turkey. This cross-sectional study was carried out with 825 health institutions established in the 18 districts of Izmir metropolitan municipality, in 2007. The total amount of health-care waste collected was 4841 tons and 621 kilograms per patient's bed in 2007. Most of the medical wastes were collected from Konak, Karsiyaka and Bornova districts and were 2308, 272 and 1020 tons, respectively. Regarding to overpopulation, the number of health institutions in these districts are more than the number of health institutions in the other administrative districts. There was a statistically significant, positive correlation between the amount of health-care waste collected and population of the 18 districts (r = 0.79, p < 0.001), and number of beds/patients (r = 0.83, p < 0.001). To provide a safe health-care waste management metropolitan municipality must provide hazardous waste separation in health institutions, establish sterilization units for infectious waste, and provide the last storage of medical waste in completely different, safe and special areas apart from the municipal waste storage areas.